2022
DOI: 10.1162/jocn_a_01872
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Expectation Improves Recognition Memory for Spatially Attended Objects

Abstract: Recent evidence suggests that temporal expectation is beneficial to memory formation. Rhythmic presentation of stimuli during encoding enhances subsequent recognition and is associated with distinct neural activity compared with when stimuli are presented in an arrhythmic manner. However, no prior study has examined how temporal expectation interacts with another important form of facilitation—spatial attention—to affect memory. This study systematically manipulated temporal expectation and spatial attention d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…As temporal patterns are part of our daily life, these resulting expectations can improve the processing of task-relevant information (Rohenkohl et al, 2012), whereas violations of expectations can also enhance selective attention (M. Tang et al, 2023;X. Tang et al, 2016), and hasten learning (Jin et al, 2020;Jones et al, 2022). It is well established that humans are able to extract regularities in the temporal structure of sensory stimuli (Ball et al, 2022;Ball, Michels, et al, 2018;Nobre & van Ede, 2018), which requires time-keeping mechanisms in the brain (Finnerty et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As temporal patterns are part of our daily life, these resulting expectations can improve the processing of task-relevant information (Rohenkohl et al, 2012), whereas violations of expectations can also enhance selective attention (M. Tang et al, 2023;X. Tang et al, 2016), and hasten learning (Jin et al, 2020;Jones et al, 2022). It is well established that humans are able to extract regularities in the temporal structure of sensory stimuli (Ball et al, 2022;Ball, Michels, et al, 2018;Nobre & van Ede, 2018), which requires time-keeping mechanisms in the brain (Finnerty et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Since the objective of this review is to elucidate whether spatial and temporal attention operate independently or interactively to enhance behavior, we have exclusively included studies that investigated their relationship. Studies that solely compared spatial and temporal attention separately (e.g., Griffin, Miniussi & Nobre, 2002 ; Sharp, Melcher, & Hickey, 2019 ; Tang et al, 2013 ) or that focused on dimensions other than the spatial and temporal ones (e.g., social orienting, Hayward & Ristic, 2015 ; memory processes; Jones et al, 2022 ) have been excluded. In the Discussion section, we summarize the main findings regarding the relationship between spatial and temporal attention and highlight some critical gaps that require to be addressed by future research.…”
Section: Introductionmentioning
confidence: 99%
“…Jones (2015) used the Posner cue task to explore stimulation with visual, auditory, and cross-modal audiovisual rhythms, and found that exogenous temporal attention and endogenous spatial attention did not interact [14]. Jones et al found that temporal attention can improve recognition memory for spatially noticed objects [31].…”
mentioning
confidence: 99%